Primary care reform in Manitoba, Canada, 2011–15: Balancing accountability and acceptability. Issue 6 (June 2019) - Kreindler, Sara A.; Metge, Colleen; Struthers, Ashley; Harlos, Karen; Charette, Catherine; Bapuji, Sunita; Beaudin, Paul; Botting, Ingrid; Katz, Alan; Zinnick, Shauna
Highlights: Policymakers strove to embed accountability mechanisms in initiatives acceptable to physicians. Some initiatives directly promoted specific behaviours (accountability) through (non-)financial support (acceptability). Others featured multiple accountability and acceptability elements, indirectly compensating for each other. Initiatives that directly linked accountability with acceptability were most easily implemented. When linked in indirect, convoluted ways, accountability and acceptability elements often clashed. Abstract: Primary care reform cannot succeed without substantive change on the part of providers. In Canada, these are mostly fee-for-service physicians, who tend to regard themselves as independent professionals and not under managerial sway. Hence, policymakers must balance two conflicting imperatives: ensuring the acceptability of renewal efforts to these physicians while enforcing their accountability for defined actions or outcomes. In its 2011–15 strategy to improve access to primary care, the province of Manitoba introduced several linked initiatives, each striving to blend acceptability- and accountability-promoting elements. Clearly delimited initiatives that directly promoted a specific observable behaviour (accountability) through financial or non-financial support (acceptability) were most successfully implemented. System-wide initiatives with complicated designs (notably a primary care network model that established formal partnership among clinics and regional health authorities) encountered greater difficulties in recruiting and sustaining physician participation. Although such initiatives offered physicians considerable decision-making latitude (acceptability), many physicians questioned the meaningfulness of opportunities for voice within a predetermined structure (accountability). Moreover, policymakers struggled to enhance the acceptability of such initiatives without sacrificing strong accountability mechanisms. Policymakers must carefully consider how acceptability and accountability elements may interact, and design them in such a way as to minimize the risk of mutual interference.